SAT0265 Evaluation of Biological Agents in Juvenile Idiopathic Arthritis, Single Center Results. (15th July 2016) - Sozeri, B.; Gunduz, Z.; Pac Kisarslan, A.; Poyrazoglu, H.; Dursun, I.; Dusunsel, R.
Abstract : Background: JIA is a chronic inflammatory joint disease with onset in children <16 years of age. Several biological agents (BAs) have become available for the treatment of JIA. Objectives: To analyze trends in prescription patterns of biological agents and drug efficacy, achievement of inactive disease and reason for switching in JIA. Methods: This was a retrospective study of children with JIA treated with biologic agent (BA) between 2006 and 2015. Efficacy was determined using the Juvenile Arthritis Disease Activity Score (JADAS)-27. Results: We enrolled total 111 patients (61female, 50 male). The JIA type differentiated was systemic JIA (sJIA) (n=16), Extended Oligo (n=21); Poly JIA (n=33);Entezitis related arthritis (ERA) (n=32); psoriatic arthritis (n=4) and undifferentiated JIA (n=5). The median age of the patients at diagnosis of JIA was 94 months [interquartile range (IQR) 60–138), while the median age at the time of treatment with first BA was 141 months (IQR 83–177). The median disease duration prior to treatment with BA was 20 months (IQR 7–48). 94 patients (84.7%) received their BA in combination with mtx (alone or with another DMARD) while 15.3% had BA alone. Pretreatment steroids was higher in sJIA with 15 (94%), than in Poly (n=20, 60%) and ERA (n=14, 45%) patients (p=0.00).The JADAS 27 was available for 94% of patients at baseline, with a median score of 18.5 and no significant variation with the subtypes (p=0.68). The median JADAS27 after prior BA was 4 (IQR 2–8). No statistically significant differences was seen in baseline CHAQ across the subtypes (p=0.32). In ERA, the median JsPD score was 4, 5 at baseline. The BAs were etanercept (ETA) (62%), adalimumab (ADA) (36%), tocilizumab (19%), infliximab (9%), canakinumab (7%), abatacept (7%) and anakinra (2.7%). ADA and ETA were preferred with equal in ERA while ETA was the first BA in other subtypes (p=0.00). 26% of patients (n=29) received more than one biologic during follow-up (2 agents, n=18; ≥3agents, n=11). Most of the switchers were in SJIA (38%, p=0.00), less often were in Poly (31%) and ERA (14%). In the switchers, median follow-up duration on BA was 13 months (range 1–69) under the first BA, 6.8 months (range 1–26) under the second and 6.5 months (range 1–19) under the third BA, (p>0.05). The reasons of switching was loss of response (58.6%, n=15), lack of effectiveness (27.5%, n=8), adverse event (13.7%, n=4), and convenience of use and patient's choice in 2 patients each (2%). At last follow up, 97 patients (87.4%) achieved inactive disease, in 78 (80%) of these patients with a first BA, 12 (12.3%) with a second BA, 4 (4%) with a third and 2 (2%) under a fourth BA. Minimal disease activity was seen in 11 patients while 3 patients were still in the active.A persisting limitation or loss of normal range of articular motion of ≥1 joint was recorded in 26 of patients (23.4%) at last follow-up. No case of cancer or death was recorded. 8 patients had developed short stature, 6 had osteoporosis, 2 had amyloidosis, 2 had neuropathic pain and 2 had glaucoma at last examination. Two patients underwent surgical intervention (hip arthroplasty and wrist arthrodesis). Conclusions: Biologic agents appear to be highly effective in children and adolescents with JIA who were resistant DMARDs. Reumatologists take into patient factors andnewly data in choosing the optimal BA Disclosure of Interest: None declared